2014
DOI: 10.12820/rbafs.v.19n2p256
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to bicycle use for transport and leisure among adults

Abstract: O objetivo do estudo foi identificar as principais barreiras e facilitadores para o uso da bicicleta no deslocamento e no lazer em adultos de Curitiba-PR. Quarenta e oito indivíduos adultos, de ambos os sexos e que apresentavam características distintas em relação ao uso da bicicleta (deslocamento, no tempo de lazer e ativistas) participaram de entrevistas em grupos focais. A análise de conteúdo foi utilizada para agrupar os relatos semelhantes, posteriormente descritos de acordo com a distribuição de frequênc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 26 publications
0
22
0
2
Order By: Relevance
“…A técnica de grupos focais foi utilizada para auxiliar a compreensão dos facilitadores para a prática de atividade física em adolescentes. Esta técnica foi utilizada anteriormente em outros estudos, com adolescentes 16 , adultos 17 e idosos 18 para investigar a prática de atividade física.…”
Section: Métodos Características Do Estudounclassified
“…A técnica de grupos focais foi utilizada para auxiliar a compreensão dos facilitadores para a prática de atividade física em adolescentes. Esta técnica foi utilizada anteriormente em outros estudos, com adolescentes 16 , adultos 17 e idosos 18 para investigar a prática de atividade física.…”
Section: Métodos Características Do Estudounclassified
“…Systematic reviews have demonstrated an inverse relationship between the perception and number of barriers and levels of PA 3,4 . Furthermore, the perceived barriers to PA can vary between age groups and according to the context of people's lives 5 , as demonstrated in several cross-sectional studies on adolescents 6,7 , adults 8,9 , and older adults 10,11 . These differences may be explained, at least in part, by social, cultural and environmental characteristics such as norms and local culture 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Several urban form and structure characteristics (presence of bike paths/ lanes, traffic density and sloped streets) and public transport characteristics (distance to destination and ease of movement 3,11 ) are associated with bicycle use, which can partly explain the difference in levels of use in different countries. However, individual aspects such as the reasons that can hinder (barriers) or promote (facilitators) bicycle use may also explain these differences 12 .…”
Section: Introductionmentioning
confidence: 99%